Age-Related Immunoreactivity Profiles to Diverse Mycobacterial Antigens in BCG-Vaccinated Chinese Population - Yang, Qing-yuan; Zhang, Yu-tong; Xiao, Jia-ni; Liang, Yu-shuo; Ji, Ping; Wang, Shu-jun; Wang, Ying; Chen, Yingying (Frontiers in Immunology, 2021)
Long-term immunoreactivity to mycobacterial antigens in Bovis Calmette-Guérin (BCG)-vaccinated population is not well investigated. Herein, 361 volunteer healthy donors (HDs) with neonatal BCG vaccination from Shanghai region (China) were enrolled. They were subdivided into ESAT-6/CFP10- (E6C10-) and ESAT-6/CFP10+ (E6C10+) groups based on gamma-interferon release assays (IGRAs). Three mycobacterial antigens, including Rv0934, Rv3006, and Rv3841, were subjected to the determination of immunoreactivity by ELISPOT assay. The immunoreactivities to three mycobacterial antigens were firstly compared among TB patients (N=39), E6C10+ HDs (N=78, 21.61% of HDs) and E6C10- HDs (N=283, 78.39% of HDs). It was revealed that Rv3006 was dominant upon M.tb infection, while Rv3841 was likely to be more responsive upon latent TB infection. In E6C10- population, the immunoreactivity to Rv3841 maintained along with aging, whereas those to Rv3006 and Rv0934 attenuated in E6C10- HDs older than 45 years old. Our study implies the shift of dominant antigens at different infection statuses, providing the clues for the selection of mycobacterial antigens in vaccine development and precision revaccination in the future.